PARASAL BİRLİĞİN ÜYE ÜLKELER AÇISINDAN FAYDA VE MALİYETLERİ - M. Kemal Değer (Ankara Avrupa Çalışmaları Dergisi)
In this study, potential benefits and costs of monetary union have been explained.The most important cost element of monetary union is that countries can't apply an independent monetary and exchange rate policy because of monetary union. At the same time both decreasing of transaction costs and disappearing of exchange rate uncertainities because of monetary union will directly or indirectly create effects that increase welfare of member countries. Monetary union has ben assetmented points of view of Monetarist and Keynesian by using cost-benefit curves. It has been concluded that monetary union can provide important benefits for member countries.Parasal birlik ve para alanları , üye ülkelerin kendi ulusal parasının ve para politikalarının kullanımı bir kenara bırakıp, aynı para biriminin kullanılması olarak tanımlanan antlaşmalardır. Parasal birliğin en yakın tarihteki uygulaması Euro'dur. Avrupa Birliğine üye ülkelerin birçoğunun katılımıyla oluşturulan bu birlik, Maastricht anlaşmasında öngörülen kriterler üzerine inşa edilmiştir.